Epigastric Pulsation: Prevalence and Association with Co-Morbidities in Saudi Population, a Cross-Sectional Descriptive Study - Manal Abdulaziz Murad; Hoda Jehad Abousada; Faisal Abdulaziz Almutairi; Emad Bani Alharbi; Khalid Saad Alrashdi; Dr. Mujib Mualla Alotaibi; Khalil Hassan Jafari; ‎‏Mohammed Oqab Althagafi; Majed Rabie Alhamdan; Saud Mohammed Alotaibi (International Journal of Innovative Research in Medical Science, 2020)
Epigastric pulsation is feeling of pulsation between the xiphoid process and the umbilicus. It can be found normally in population (especially in thin lean people) or abnormally as a sign or a symptom of other diseases, such as heart, liver, and aortic disease. This descriptive study, using a questionnaire, assesses the prevalence of epigastric pulsation among 878-case sample, the association with other diseases especially DM, smoking history and obesity. Prevalence was 51.7%. Most common disease to be associated with epigastric pulsation is gastrointestinal disease. No association was found with DM. Positive association was found between smoking history and BMI, and the feeling of epigastric pulsation.